Reference without referents - Sainsbury, R. M. (Richard Mark) (Clarendon Press, 2005)
Reference is a central topic in philosophy of language. This book sets out a new approach to the concept, which promises to bring to an end some long-standing debates in semantic theory. It also includes an historical survey. It will be of interest to those working in logic, mind, and metaphysics.